ANALISIS PENGENDALIAN PERSEDIAAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY PADA UKM TO DURI - Nurwahida Nurwahida; Amiruddin Amiruddin; Leny Susilawati Anggraini (Tinta Nusantara 2018 Vol.1, 2022)
The purpose of this research is to find out when SMEs determine the economic order level using the Economic Order Quantity method. From the results of the analysis of the discussion carried out by the author. The researcher reveals that there is a great influence from the application of the Economic Order Quantity (EOQ), Safety Stock and Reorder Point methods to inventory, if the Economic Order Quantity (EOQ), Safety Stock and Reorder Point methods are not applied properly. good, it will affect the raw material for fish fillets, they will run out of stock, and the order will be slow to arrive, if this continues to happen it will impact on the decreased ampalang production.